Internal Migration in Ethiopia Evidence from a Quantitative and Qualitative Research Study - Bundervoet, Tom (The World Bank, 2018)
In many developing countries, disparities in living standards between lagging and leading areas, or between rural and urban areas, are large. The spatial disparities in living standards offer a compelling motivation for people in lagging areas to move closer to economic density. Ethiopia too has a history of trying to prevent or limit internal migration. A small but growing micro-economic empirical literature finds large welfare effects of internal migration. While a population census offers the best source of data to study internal migration, the most recent census was conducted in 2007. The next census is planned to happen towards end 2018, while the census microdata will likely not be available before 2020. As a result, this paper uses three rounds of the labor force surveys (LFS) and look at trends and patterns of internal migration in Ethiopia and the characteristics of internal migrants. to contextualize the quantitative analysis, a qualitative research study with rural migrants in urban areas was conducted in May 2017. This note takes a closer look at the scale and nature of internal migration in Ethiopia. This note os organized as follows: section one gives introduction. Section two presents the scale and pattern of internal migration, focusing particularly on rural-to-urban migration. Section three focuses on the characteristics and motivations of migrants, focusing on push and pull factors and disaggregating by type of migration. The main findings from the qualitative research are summarized in section four. The final section concludes and formulates some tentative recommendations